Translation Practice of Kh. O. Alchevska in the Context of Ukrainian Literary Europeanism - Мариняк, Руслана; Казімір, Ірина (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The paper is concerned with the translation practice of Kh. O. Alchevska. The authors tried to prove that attention to translation was not a stochastic phenomena, but it became a conscious choice of that area of focus and the result of mainstreaming into Europeanism of the Ukrainian literature in the early 1900s. They explained that the concepts of Europeanism, defined by the Ukrainian best translators in their theoretical works, letters and discussions at the turn of ХХ century, overtly or covertly influenced on Kh. O. Alchevska’s refocusing from poeticizing to translating. The value of the translators’ work was stressed as the translators introduced the Ukrainian readers to the European literary advances, the access to which was more than limited at that time.